Comparison of first trimester transvaginal anatomy scan to the second trimester structural survey in normal weight and obese populations: a pilot study. (2nd September 2018) - McCormick, Anna; Anaya, Heather; Mehendale, Ramkrishna; Fogg, Louis; Roche, Michael; Abramowicz, Jacques
Abstract: Purpose: To compare visualization of first trimester fetal anatomic transvaginal ultrasound (TVUS) to the second trimester transabdominal anatomic ultrasound (TAU) in normal weight and obese patients. Materials and methods: In a prospective cross-sectional study design, 25 women underwent a TVUS between 12 and 14 weeks, and a TAU at 18–22 weeks. For each anatomic structure, the percentage of patients achieving optimal visualization was recorded. Risk ratios for visualizing a structure in the second trimester versus the first were calculated. Results: Twenty-five patients underwent a TVUS and 24 completed the TAU. The average BMI in the obese and nonobese groups was 34 kg/m 2 and 23 kg/m 2, respectively. All structures were more consistently visualized during the TAU for the both groups. The cardiac views, hands and feet were more difficult to visualize in all the patients at both scan times but were more frequently visualized in the TAU. For the obese patients, hands, feet, cardiac and spine views were less frequently visualized in both the scans. The posterior fossa and profile views were more difficult to obtain in the TVUS. Conclusions: The first trimester TVUS detects many of the structures assessed during an anatomic survey; however, it is not superior to the second trimester TAU in normal weight and obese patients.